Complex role of SIRT6 in NF-κB pathway regulation - Irene Santos-Barriopedro; Alejandro Vaquero (Molecular & Cellular Oncology, 2018)
The NF-κB pathway regulates cell physiology under stress conditions. We have recently described a novel NF-κB regulatory mechanism, by which SIRT6 induces cysteine monoubiquitination of the methyltransferase SUV39H1. This causes SUV39H1 dissociation from the gene encoding the NF-κB inhibitor IκBα,  increasing its expression and leading to NF-κB pathway inactivation.